Preferences of Millennial Generation in Choosing Islamic Banking Services: A Case Study - Aulia, Aulia; Hidayat, M; Syah, Firman (Borong Newinera Publisher, 2025)
This study aims to determine the preferences of the millennial generation in choosing Islamic banking services in Makassar City. This research is a descriptive study with a quantitative approach with data analysis techniques using simple linear regression and hypothesis testing consisting of t test and the coefficient of determination. The results of the study show that the Millennial Generation's consumer preferences have a positive and significant influence on the Millennial Generation's decision to choose Sharia Banking Services in Makassar City. The sharia marketing concept is expected to be applied in supporting the development of sharia products, especially for the millennial generation, which currently has a large population.